Exploring Ethnomathematics in the Menara Kudus as a Learning Resource for Geometry - Lukman Harun; Aunul Ma'bud; Putri Ayu Trihara (Department of Mathematics Education Program IPI Garut, 2024)
Pembelajaran matematika siswa akan lebih bermakna ketika materi berkaitan dengan kondisi yang sesuai dengan apa yang ada di sekitarnya. Pentingnya penelitian ini dilakukan karena Menara Kudus yang merupakan salah satu peninggalan budaya dapat dilestarikan melalui pembelajaran disekolah sebagai sumber belajar yang bermakna bagi siswa. Penelitian ini bertujuan untuk mengeksplorasi dan memperdalam etnomatematika di Menara Kudus sebagai sumber belajar bagi siswa. Dalam penelitian ini menggunakan jenis penelitian deskriptif kualitatif dengan pendekatan etnografi. Teknik pengumpulan data menggunakan observasi dan pencatatan. Teknik analisis data yang digunakan reduksi data, penyajian data dan penarikan kesimpulan. Objek pengamatan pada kegiatan ini adalah bangunan Menara Kudus. Simpulan dari penelitian ini didapatkan bahwa geometri yang terdapat pada bangunan Menara kudus adalah bagian dasar menara yang menampilkan banyak dekorasi batu bata dan dapat dimodelkaan menggunakan geometri persegi panjang, persegi, segitiiga, dan berlian. Untuk badan menara dimodelkan pelat dan batu bata menggunakan geometri lingkaran, persegi panjang, dan berlian. Sebaliknya tangga tower dengan dinding dan pintu dapat dimodelkan sebagai trapesium, segitiga sama kaki, segitiga siku-siku, trapesium. Students' mathematics learning will be more meaningful when the material is related to conditions that are in accordance with what is around them. The importance of this research is that the Menara Kudus, which is one of the cultural heritages, can be preserved through learning at school as a meaningful learning resource for students. This research aims to explore and deepen ethnomathematics at Menara Kudus as a learning resource for students. This research uses a qualitative descriptive research type with an ethnographic approach. Data collection techniques use observation and recording. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The object of observation in this activity is the Menara Kudus building. The conclusion from this research is that the geometry found in the Menara Kudus building is the base of the tower which displays many brick decorations and can be modeled using rectangular, square, triangle and diamond geometries. For the tower body, plates and bricks were modeled using circle, rectangle and diamond geometry. On the other hand, tower stairs with walls and doors can be modeled as trapezoids, isosceles triangles, right triangles, trapezoids.